Effect of a 12-h increment in the short-term treatment regimen on ovarian status, estrus synchrony, and pregnancy rate in artificially inseminated dairy goats - Carvalho-de-Paula, Cleber Jonas; Goncalves Souza-Fabjan, Joanna Maria; Goncalves, Joedson Dantas [UNESP]; Dias, Jenniffer Hauschildt; Souza, Guilherme Nunes de; Franco Oliveira, Maria Emilia [UNESP]; Fonseca, Jeferson Ferreira (Elsevier B.V., 2020)
This study was conducted to assess effects of two hormonal treatments on ovarian follicular status, estrous synchrony and fertility in dairy goats during the non-breeding season when duration of progestogen device use varied by 12 h. In both experiments, does were administered 60 mg of medmxyprogesterone acetate via intravaginal devices, respectively, for 6 and 6.5 d (G6 and G6.5). At 24 or 36 h before device removal, 200 IU of eCG im and 30 mu g d-clopmstenol im were administered. In Experiment 1 (n = 24), data related to sexual behavior and that were collected using ovarian ultrasonography were recorded, and in Experiment 2 (n = 83) fertility was assessed after Flexible Time Artificial Insemination (FxTAI). The interval from device removal to estrus was shorter (P < 0.05) after imposing the G6.5 treatment regimen. Diameter of largest and second-largest ovarian follicles and interval from device removal to ovulation were similar (P> 0.05) between groups. The does treated with the G6.5 hormonal regimen had greater estrous synchrony, associated with greater development of largest follicles at the time of device removal, which might have led to a lesser fertility rate (P > 0.05). Conversely, treatment with the G6 hormonal regimen resulted in a greater conception rate. In conclusion, increasing time the intravaginal device is inserted from 6 to 6.5 d resulted in greater estrous synchrony, advanced ovarian follicular development, abnormal CL function and lesser pregnancy rates in artificially inseminated dairy goats when there were treatments during the non-breeding season.
Keywords: AI; Anestrus; Caprine; Corpora Lutea; Follicular Dynamics; Ultrasound